The Impact of Face Filter Use on Self-Image and Narcissistic Communication on TikTok - Rosy Febriani Daud; Siti Rohmah; Muhammad Nur (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2026)
This research is motivated by the widespread use of face filters on the Tiktok platform, which significantly influences how individuals construct their self-image and present themselves through visual communication. The research questions are: (1) how the use of face filters influences the formation of self-image among Tiktok users, and (2) how the use of face filters encourages the emergence of narcissistic communication among users. The purpose of this research is to analyze the impact of face filter use on self-perception and narcissistic communication patterns, and to explain the relationship between digital identity construction and self-presentation practices reinforced by the Tiktok algorithm. This research uses a descriptive qualitative method with data collection techniques in the form of content observation, visual analysis of face filter use, and semi-structured interviews with active Tiktok users aged 18–25 who utilize face filters in content creation. Data are analyzed using the Media Effects theory approach and the concept of narcissistic communication to gain a deeper understanding of the phenomenon. The study's findings suggest that the use of face filters triggers the formation of an unrealistic idealized self-image, increases dependence on public validation, and fosters narcissistic communication tendencies such as self-promotion, attention-seeking, and excessive identity curation. Furthermore, TikTok, through its visual features and algorithmic mechanisms, reinforces narcissistic culture by rewarding filtered content with likes, comments, and increased exposure. This research confirms that face filters function not only as aesthetic tools but also as technologies that shape users' digital identities and communication dynamics.